2018
DOI: 10.1002/ieam.4086
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate sensitivity thresholds for sediment in Virginia streams

Abstract: Sediment is the most commonly identified pollutant associated with macroinvertebrate community impairments in freshwater streams nationwide. Management of this physical stressor is complicated by the multiple measures of sediment available (e.g., suspended, dissolved, bedded) and the variability in natural "healthy" sediment loadings across ecoregions. Here we examine the relative importance of 9 sediment parameters on macroinvertebrate community health as measured by the Virginia Stream Condition Index (VSCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The stronger relationship between feeding preferences and embeddedness may be attributed to reduction in interstitial spaces of the stream bed, limiting the food available for both benthic and specialist feeders. Similarly, Govenor et al (2019) found that embeddedness was the most important form of sediment for stream macroinvertebrates in Virginia; such invertebrates are commonly eaten by benthic and specialist feeders. A causative link between silt cover and reproductive traits remains unclear because few fish we collected were apparently actively reproducing.…”
Section: Trait Responses To Deposited Sedimentmentioning
confidence: 93%
See 1 more Smart Citation
“…The stronger relationship between feeding preferences and embeddedness may be attributed to reduction in interstitial spaces of the stream bed, limiting the food available for both benthic and specialist feeders. Similarly, Govenor et al (2019) found that embeddedness was the most important form of sediment for stream macroinvertebrates in Virginia; such invertebrates are commonly eaten by benthic and specialist feeders. A causative link between silt cover and reproductive traits remains unclear because few fish we collected were apparently actively reproducing.…”
Section: Trait Responses To Deposited Sedimentmentioning
confidence: 93%
“…managers understand anthropogenic influences on fish assemblages. Schwartz et al (2011) examined relationships between functional traits and turbidity, and Govenor et al (2019) found embeddedness to be the most impactful form of sediment to macroinvertebrate communities. However, few studies explicitly link traits within local fish assemblages to in-stream sediment deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the HI reflects the thickness of the loop shape; a larger absolute magnitude means that there is a greater difference between the rising and falling limbs of the flow event, yielding a wider, more circular looking loop. 42 The absolute magnitude of HI may reflect antecedent flow conditions or variations in Q through the event. 43 Three main shapes of hysteresis loops (circular, figure eight, and linear) are commonly observed in nature and provide insight into the behavior of the dependent variable during high-flow events.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Stroubles Creek has been extensively studied since the early 1900s, with much of the work focusing on bacterial ecology and water quality. , Over the past few decades, research projects have diversified to include a variety of overlapping fields, including hydrology, , land use and imaging, , restoration and monitoring, , ecosystem metabolism and biogeochemistry, , and organismal studies both within the stream and along the riparian corridor. , Pressures from the urbanizing watershed, Virginia Tech’s expansion, and climate change have continued to increase anthropogenic stress on this water body. One specific pressure is the use of road salts by both the Town of Blacksburg and the Virginia Tech Department of Facilities Operations, as well as the latter’s use of de-icing brine obtained from its Central Steam Plant.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation